2016
DOI: 10.1007/s10708-016-9728-9
|View full text |Cite
|
Sign up to set email alerts
|

Facts behind the myth of conservative rurality: major determinants of rural farmers’ innovation adoption decisions for sustainable agriculture

Abstract: Even though development is about change, conservative rurality associated with the refusal of rural societies to submit to technological, livelihood and socio-cultural changes has not received adequate focus in development studies and practice. Using the case of selected rural communities in Ghana and their response to the mass cocoa spraying intervention of government, the paper discusses the determining factors that influence innovation adoption decisions of rural farmers. The study followed mixed methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…There is little evidence that supports more family rejection or acceptance among rural LGBTQ+ adolescents compared to their urban counterparts. Despite more socially and religiously conservative families in rural areas (Adjei et al, 2017; Han, 2018; Han et al, 2020), it remains unclear what aspects of family (e.g., faith, fear, ability to adjust/adapt to LGBTQ+ identity), aside from family support, are most influential for rural LGBTQ+ adolescents’ mental well-being. For instance, the Family Acceptance Project (FAP) found that family-rejecting behaviors may be motivated by care, concern, fear, and misinformation, but due to the lack of rural family perspective in the literature, understanding of psychosocial protective and risk factors for LGBTQ+ adolescents’ mental well-being at the interpersonal level remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence that supports more family rejection or acceptance among rural LGBTQ+ adolescents compared to their urban counterparts. Despite more socially and religiously conservative families in rural areas (Adjei et al, 2017; Han, 2018; Han et al, 2020), it remains unclear what aspects of family (e.g., faith, fear, ability to adjust/adapt to LGBTQ+ identity), aside from family support, are most influential for rural LGBTQ+ adolescents’ mental well-being. For instance, the Family Acceptance Project (FAP) found that family-rejecting behaviors may be motivated by care, concern, fear, and misinformation, but due to the lack of rural family perspective in the literature, understanding of psychosocial protective and risk factors for LGBTQ+ adolescents’ mental well-being at the interpersonal level remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one might think of the idea that agricultural sectors are naturally conservative and resistant to technological change. However, empirical studies have shown that innovation adoption decisions of rural societies are rooted in their awareness, cost and benefit factors and applicability of introduced technology rather than the myth of adherence to socio-cultural heritage [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…Innovation resistance in rural communities is not the same as innovation inertia, i.e., not reducible to the status-quo satisfaction aspect of passive innovation resistance (Heidenreich and Handrich, 2015). In fact, Adjei et al (2017), p.2) dismissed the idea that rural communities were less prepared to accept and use innovation. Furthermore, Cohen (2011, p.213) reasoned that conservatism, often found in rural communities, does not oppose new creations as long as they leave the "old creations intact; " reminiscent of Sheth's (1981) observation that the strength of existing habits could nurture resistance to a new technology.…”
Section: Innovation Resistance In a Rural Contextmentioning
confidence: 99%